Team learning linking paradoxical team leadership and team performance: a moderated mediation study - Pas, Marloes (2019)
Teamwork, and in turn, team leadership, are gaining popularity in today’s dynamic and complex economy. Therefore, the influence of team leadership has been subject to ample research. In addition to team leadership, team learning and team psychological safety are two key terms commonly analysed in team performance studies. Using a moderated mediation model, this thesis analyses the effect of paradoxical team leadership and its influence on team performance through exploitative and exploratory team learning. Also, the moderation effect of psychological safety on the relationship between paradoxical team leadership and exploitative and exploratory team learning is analysed. The study included 33 teams (124 individuals) from different industries. Our findings suggest that paradoxical team leadership has a positive influence on exploitative team learning, exploratory team learning and team performance. In addition to that, exploratory team learning mediated the paradoxical team leadership – team performance relationship. In contrast with our expectations, exploitative team learning did not mediate the relationship between paradoxical team leadership and team performance. Neither did team psychological safety moderate the relationship between paradoxical team leadership and exploitative and exploratory team learning. Lastly, the moderated mediation effect was insignificant. Based on this research, team leaders are urged to adopt a paradoxical leadership style in order to stimulate team learning and team performance.